β-In₂S₃ nanoplates for ultrafast photonics - Li, Xiaohui (2022)
The technological revolution of two-dimensional (2D) materials provides vitality for ultrafast optics. Compared with other 2D materials, indium sulfide (In2S3) has become an attractive candidate material in the field of nonlinear optics because of its high carrier mobility, ultrafast photoelectric sensitivity, medium band gap, and high absorption coefficient. However, its nonlinear optical effects have rarely been studied. In this work, we synthesized 2D β-In2S3nanoplates using the hydrothermal method. The saturable absorber based on β-In2S3nanoplates has been investigated. The experimental results demonstrated that the modulation depth and saturable intensity of β-In2S3are measured as 2.32% and 18.4 MW·cm-2, respectively, which indicates that β-In2S3has great potential in ultrafast optics among emerging nonlinear optical materials. Using such unprecedented properties, the mode-locked fiber laser with 247th (1.92 GHz) harmonic mode locking is realized in the C-band for the first time to our knowledge. This paves the way for exploring β-In2S3as an outstanding nonlinear material for high-performance ultrafast optics.